Solid solutions of InSb-ZnS heterosystem — primary converters of semiconductor sensors - I. A. Kirovskaya; N. V. Chernous; E. V. Mironova; А. О. Ekkert (Омский научный вестник, 2021)
Using the specifically developed method, solid solutions of the AIIIBV (InSb), AIIBVI (ZnS) type semiconductor compounds of various composition (InSb)x (ZnS)1-x have been obtained. According to the results of the performed X-ray, micro-, electron-microscopic studies, the obtained solid solutions are certified as substitutional solid solutions with a cubic sphalerite structure, data on multicomponent diamond-like semiconductors has been enlarged. The chemical composition of the solid solutions surfaces and binary components of the InSb-ZnS system exposed in air and in high-vacuum, high-temperature conditions have been determined. According to the results of the acid-base properties studies, the surfaces of the InSb-ZnS system components exposed in the air are assigned to the weakly acidic region (pHiso<7). The views on the predominant relative contribution of Lewis acid sites and the increased activity of surfaces toward the main gases have been stated and proved. The interrelated consistent patterns of changes in the composition of bulk and surface properties have been established. The practicability of their use for a less labour consuming search for the advanced materials intended for the sensor technology has been shown. The obtained solid solutions, specifically those with the lowest pHiso, are recommended for the manufacture of the sensors for the main gases, particularly NH3, trace contamination.